2017
DOI: 10.3389/fncel.2017.00412
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Stress-Induced Increase in the Membrane Expression of the Water-Permeable Channel Aquaporin-4 in Astrocytes Is Regulated by Caveolin-1 Phosphorylation

Abstract: The reperfusion of ischemic brain tissue following a cerebral stroke causes oxidative stress, and leads to the generation of reactive oxygen species (ROS). Apart from inflicting oxidative damage, the latter may also trigger the upregulation of aquaporin 4 (AQP4), a water-permeable channel expressed by astroglial cells of the blood-brain barrier (BBB), and contribute to edema formation, the severity of which is known to be the primary determinant of mortality and morbidity. The mechanism through which this occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 58 publications
(65 reference statements)
2
16
0
Order By: Relevance
“…We previously showed that Nilotinib was detected in the human CSF 4 hours after administration but inhibition of CSF Abl extended up to 6 hours, 16 suggesting that free CSF Nilotinib may not be the final or total concentration of drug that enters the brain. Nilotinib exhibits strong and irreversible binding to its target and the level of CSF Nilotinib may reflect the dynamic pharmacological properties of tyrosine kinase inhibitors via interaction with the ATP-binding cassette efflux transporters, [34][35][36] According to the Novartis Investigator Brochure (IB), Nilotinib has a moderate passive permeability and is a PgP inhibitor with an IC50 of 1.7 μmol/L, and this is likely not relevant at the BBB given the low Cmax of 0.06 μmol/L. Furthermore, our mouse studies showed that Nilotinib concentration in the brain increased in an underproportional manner with dose.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that Nilotinib was detected in the human CSF 4 hours after administration but inhibition of CSF Abl extended up to 6 hours, 16 suggesting that free CSF Nilotinib may not be the final or total concentration of drug that enters the brain. Nilotinib exhibits strong and irreversible binding to its target and the level of CSF Nilotinib may reflect the dynamic pharmacological properties of tyrosine kinase inhibitors via interaction with the ATP-binding cassette efflux transporters, [34][35][36] According to the Novartis Investigator Brochure (IB), Nilotinib has a moderate passive permeability and is a PgP inhibitor with an IC50 of 1.7 μmol/L, and this is likely not relevant at the BBB given the low Cmax of 0.06 μmol/L. Furthermore, our mouse studies showed that Nilotinib concentration in the brain increased in an underproportional manner with dose.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection also stimulates the AQP3 level dependent production of proinflammatory cytokines IL-6, IL-8, and TNFα, which adds up to the progression of gastric carcinomas [ 101 ]. Oxidative stress induces an increase in the membrane expression of AQP4 in astrocytes and is regulated by caveolin-1 phosphorylation [ 102 ]. The oxidative stress induced increase in the membrane expression of AQP4 was inhibited by the antioxidant N-acetylcysteine (NAC) [ 102 ].…”
Section: Role Of Aquaporins In Oncogenic Pathwaysmentioning
confidence: 99%
“…Oxidative stress induces an increase in the membrane expression of AQP4 in astrocytes and is regulated by caveolin-1 phosphorylation [ 102 ]. The oxidative stress induced increase in the membrane expression of AQP4 was inhibited by the antioxidant N-acetylcysteine (NAC) [ 102 ].…”
Section: Role Of Aquaporins In Oncogenic Pathwaysmentioning
confidence: 99%
“…Moreover, NO also causes oxidative stress and death of neurons. Interestingly, another paper by Bi et al showed that hydrogen peroxide (H 2 O 2 ) induces a significant increase in the AQP4 levels in brain astrocytes, and elimination of the oxidative stress depresses the increase [19]. They also showed that H 2 O 2 increases AQP4 plasma membrane expression and that this change is independent of de novo AQP4 synthesis.…”
mentioning
confidence: 99%